Four papers on the economics of technology - Waters, James (2015)
This dissertation consists of four chapters on the economics of technology. The chapters study different aspects of innovation generation and diffusion. In broad terms, chapter one looks at how innovation spreads by social contact, while chapter two looks at welfare consequences of diffusion. Chapter three examines how information sources affect diffusion, and chapter four looks at the relation of finance with innovation generation.